The signal crayfish Pacifastacus leniusculus (Dana, 1852) (Crustacea, Decapoda) is threatening the near future of Margaritifera margaritifera Linnaeus, 1758 (Bivalvia, Unionoida) in the Negro River (NW Zamora, Spain) - J. Morales (Animal Biodiversity and Conservation)
We studied the incidence of the signal crayfish on a population of Margaritifera margaritifera in the Negro River (Zamora, Spain) during the summers of 2019 to 2022. The incidence of predation was assessed as a mortality factor in relation to floods and the hydrology of the river. The crayfish were trapped in a small plot of high pearl mussels density monitored since 2002, and collected each summer since 2019, during which time their abundance increased (65 % in three years). Simultaneously, we counted the shells carried by the floods to the gravel riverbanks. The incidence of floods was stable between 2019 and 2022 (10.3 % to 19.4 % of mortality), while at the bottom of the river the mortality of pearl mussels increased due to predation from 2.7 % to 43.3 %. During the 2022 dry season, 29 pearl mussels that had recently died and whose shell edges were widely gnawed by crayfishes were collected from the plot. The shells appeared bitten only in the contour exposed above the gravel, ruling out the possibility that the marks could be the effect of the scavenging of dead specimens by the crayfish. Low intensity trapping barely affected the crayfish population, since the following year their abundance in the controlled section had recovered.